Ginsenoside Rh2 inhibits breast cancer cell growth via<?A3B2 ACK?>ERβ-TNFα pathway - Peng Kunjian; Luo Tiao; Li Jijia; Huang Jingjia; Dong Zizeng; Liu Jia; Pi Chaoqiong; Zou Zizeng; Gu Qin; Liu Ousheng; Zhang Jian-Ting; Luo Zhi-Yong (Acta Biochimica et Biophysica Sinica)
Ginsenoside Rh2 is one of rare panaxidiols extracted from Panax ginseng and a potential estrogen receptor ligand that exhibits moderate estrogenic activity. However, the effect of Rh2 on growth inhibition and its underlying molecular mechanism in human breast cells are not fully understood. In this study, we tested cell viability by MTT and colony formation assays. Cell growth and cell cycle were determined to investigate the effect of ginsenoside Rh2 by flow cytometry. The expressions of estrogen receptors (ERs), TNFα, and apoptosis-related proteins were detected by qPCR and western blot analysis. The mechanisms of ERα and ERβ action were determined using transfection and inhibitors. Antitumor effect of ginsenoside Rh2 against MCF-7 cells was investigated in xenograft mice. Our results showed that ginsenoside Rh2 induced apoptosis and G1/S phase arrest in MCF-7 cells. Treatment of cells with ginsenoside Rh2 down-regulated protein levels of ERα, and up-regulated mRNA and protein levels of ERβ and TNFα. We also found that ginsenoside Rh2-induced TNFα over-expression is through up-regulation of ERβ initiated by ginsenoside Rh2. Furthermore, ginsenoside Rh2 induced MCF-7 cell apoptosis via estrogen receptor β-TNFα pathway in vivo. These results demonstrate that ginsenoside Rh2 promotes TNFα-induced apoptosis and G1/S phase arrest via regulation of ERβ.